Performance of Some Grape Cultivars for Commercial Cultivation in West Bengal - Pal, Ranjit; Deb, P.; Ghosh, S. N. (International Journal of Bio-resource and Stress Management, 2018)
The experiment was carried out for two consecutive years during 2010 and 2012 at the experimental grape orchard at Horticultural Research and Development Farm, Govt. of W.B, Taldangra, Bankura. The experiment was conducted in randomized block design with four replications. The vines were trained on ‘Y’-trellies system and spacing of 2×3 m2. The vine was pruned on 30th January. As per fruit maturity, the cultivars Pusa Navrang were considered to be the earliest harvesting.Among the twelve cultivars, maximum fruit yield was recorded in Arka Neelamani (7.81 kg vine-1). The number of bunches/vine were varied significantly among the cultivars with number of bunches/vine highest in cultivar Arka Trishna. But bunch weight was highest in cultivar Arkavati (264.2 g). Size of the bunch was maximum in Arka Kanchan. However, different cultivars of grape exhibited significant variation with respect to average ten berries weight. The ten berries weight was highest in Arka Magestic. The cultivars Arka Trishna gave the highest juice %, total soluble solids, lowest acidity, highest TSS/acid ratio and sugar content. Ascorbic acid content highest was recorded from cultivar Pusa Navrang as compared to other cultivars. Incidence of major insects and diseases determine the economic feasibility of a cultivar in the area. It appears from the good performed cultivars less incidence of major insects and diseases during flowering to fruiting period. On the basis of marketable yield, fruit quality and tolerance to pest, cultivars Arka Neelamani for table purpose can be recommended for commercial cultivation under Bankura conditions of West Bengal.